2022
DOI: 10.3390/ijerph191811375
|View full text |Cite
|
Sign up to set email alerts
|

Level of Concern, Spending, and External Support Related to COVID-19: A Comparison between Working and Non-Working Older Adults

Abstract: This study compared levels of concern, spending, and use of external support by working status among older adults in the U.S. during the COVID-19 pandemic. It assessed whether work influences these variables related to wellness. Data from 2489 older adults from the 2020 U.S. Health and Retirement Study were analyzed using multiple linear and logistic regression. Older adults who worked had lower concerns about the pandemic (β = −0.28, p = 0.048), were less likely to increase their spending (OR = 0.74, p = 0.04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Having friends who were affected and not being personally affected with COVID-19 were also predictive of a positive attitude towards mandatory and seasonal vaccination. A previous study has shown that higher levels of concern were associated with having friends and family members being affected by COVID-19 [25], which corroborated our results as well.…”
Section: Discussionsupporting
confidence: 92%
“…Having friends who were affected and not being personally affected with COVID-19 were also predictive of a positive attitude towards mandatory and seasonal vaccination. A previous study has shown that higher levels of concern were associated with having friends and family members being affected by COVID-19 [25], which corroborated our results as well.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, if such contacts cannot be avoided, they cannot reduce the number of people they come into contact with. Married people may be more worried about household members' infections through out-of-home social contacts, and so decrease the number of social contacts ( Yu et al, 2022 ). If people lived in larger households, they were prone to contact more people during daily activities.…”
Section: Discussionmentioning
confidence: 99%